Bibliometric Analysis of 5G Nircable Networking Technology - Deby Andriansah; Putri Alya Nur Faizah (Westscience Press, 2024)
Technological leadership is the most important factor in the current technological development in Indonesia. One of the greatest technological advances of the modern era is the emergence of 5G wireless networks, which significantly increase network capacity, speed, and efficiency. This is the most important factor in the development of smartphone communication technology. With a latency that is noticeably higher than 4G, users can download and upload files in a significantly shorter amount of time. This study uses bibliometric methods with the aim of analyzing the capabilities of 5G wireless technology from related studies.